2022
DOI: 10.52459/josstt25220822
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Determinants of Faculty Research Productivity in a Level-III Philippine State College

Abstract: This paper explores the extent of research productivity and its socio-demographic determinants among faculty members in a level-III state college in the Philippines. The results aim to influence the decision-making on identifying appropriate interventions to further enhance research productivity and encourage faculty members to engage in research undertakings. The results suggest that socio-demographic characteristics of faculty members such as age, administrative designation, and supervision of graduate resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Research conducted by Nasution (2006) revealed that some faculty stated that it was a requirement for them to make professional and academic presentations and publish their research in academic journals. The findings of Ambong et al (2022) showed that faculty members reported having refereed publications in the past five years comprised 15.92% (n=43) of the total tenured faculty members. Among these faculty members, 70.09% have published in refereed journals, and 20.93% have published in refereed journals and conference proceedings.…”
Section: Literature Review 21 Functions Of Higher Education Facultymentioning
confidence: 99%
“…Research conducted by Nasution (2006) revealed that some faculty stated that it was a requirement for them to make professional and academic presentations and publish their research in academic journals. The findings of Ambong et al (2022) showed that faculty members reported having refereed publications in the past five years comprised 15.92% (n=43) of the total tenured faculty members. Among these faculty members, 70.09% have published in refereed journals, and 20.93% have published in refereed journals and conference proceedings.…”
Section: Literature Review 21 Functions Of Higher Education Facultymentioning
confidence: 99%